Using the FDA’s Fish and Fishery Products Hazards and Controls Guidance to Develop HACCP Plans for Fish and Fisheries Products - Razieh Farzad (EDIS, 2025)
This Ask IFAS document is the third in the Seafood Guide series and provides information to the seafood industry on how to develop a seafood HACCP plan effectively. Written by Razieh Farzad, and published by the UF/IFAS Department of Food Science and Human Nutrition, February 2025.